RISET UNGGULAN TERPADU: KAJIAN BIBLIOMETRIKA - Tambunan, Kamariah (BACA: Jurnal Dokumentasi dan Informasi, 2013)
This study aims to know the results of integrated featured research (IFR) activities, covering the number of the researches, the scoup of research fields, and the affiliations of research. Moreover, this study is for understanding the scientific researches resulted from the IFR, the fields, the types of the research documents and the authors’ ratio. The source of data was taken from “Tracking Hasil Riset Unggulan Terpadu” (Tracking of the IFR) publication year 2000, 2001, 2002, 2004, 2005 and 2006. The study showed that there are 372 IFR’s titles which covering 14 fields. The most frequently appeared field is thetechnology of agricultural products, i.e. 69 titles (18,55%). The most common affiliation is from university, i.e. 279. The IFR resulted in 2.188 scientific publications, and at most, i.e. 1.301 titles (59,46%) are from the seminar papers and the like, nationally and internationally. The scientific research publications published at most in the year 1999, i.e. 248 titles (11,33%). If they are seen from the author collaboration side then the scientific research written by the collaborating authors are more than those which written by the single author.